The γ-ray spectrum of the core of Centaurus A as observed with H.E.S.S. and Fermi-LAT - Abdalla, Hassan; Glawion, Dorit; Jankowsky, Felix; Mohamed, Mahmoud; Quirrenbach, Andreas; Schwemmer, Stephanie; Wagner, Stefan (Arxiv, 2018)
Centaurus A (Cen A) is the nearest radio galaxy discovered as a very-high-energy (VHE; 100 GeV-100 TeV) $γ$-ray source by the High Energy Stereoscopic System (H.E.S.S.). It is a faint VHE $γ$-ray emitter, though its VHE flux exceeds both the extrapolation from early Fermi-LAT observations as well as expectations from a (misaligned) single-zone synchrotron-self Compton (SSC) description. The latter atisfactorily reproduces the emission from Cen A at lower energies up to a few GeV. New observations with H.E.S.S., comparable in exposure time to those previously reported, were performed and eight years of Fermi-LAT data were accumulated to clarify the spectral characteristics of the $γ$-ray emission from the core of Cen A. The results allow us for the first time to achieve the goal of constructing a representative, contemporaneous $γ$-ray core spectrum of Cen A over almost five orders of magnitude in energy. Advanced analysis methods, including the template fitting method, allow detection in the VHE range of the core with a statistical significance of 12$σ$ on the basis of 213 hours of total exposure time. The spectrum in the energy range of 250 GeV-6 TeV is compatible with a power-law function with a photon index $Γ=2.52±0.13_{stat}±0.20_{sys}$. An updated Fermi-LAT analysis provides evidence for spectral hardening by $ΔΓ\simeq0.4±0.1$ at $γ$-ray energies above $2.8^{+1.0}_{-0.6}$ GeV at a level of $4.0σ$. The fact that the spectrum hardens at GeV energies and extends into the VHE regime disfavour a single-zone SSC interpretation for the overall spectral energy istribution (SED) of the core and is suggestive of a new $γ$-ray emitting component connecting the high-energy emission above the break energy to the one observed at VHE energies.